2016
DOI: 10.1111/jeea.12178
|View full text |Cite
|
Sign up to set email alerts
|

The Right Amount of Trust

Abstract: We investigate the relationship between individual trust and individual economic performance. We find that individual income is hump-shaped in a measure of intensity of trust beliefs. Our interpretation is that highly trusting individuals tend to assume too much social risk and to be cheated more often, ultimately performing less well than those with a belief close to the mean trustworthiness of the population. However, individuals with overly pessimistic beliefs avoid being cheated, but give up profitable opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(34 citation statements)
references
References 27 publications
2
31
0
1
Order By: Relevance
“…Putting these insights together, one might expect a concave or even hump-shaped relationship between trust behavior and earnings (cf. Butler et al, 2012a). If trust behavior, in turn, varies positively with trust beliefs and individuals have self-interested money-maximizing preferences and, moreover, are interacting with a fixed population, one would expect earnings to be maximized when beliefs are correct: Miscalibrated trust beliefs should only reduce economic performance.…”
Section: The Economic Cost Of False Consensusmentioning
confidence: 99%
“…Putting these insights together, one might expect a concave or even hump-shaped relationship between trust behavior and earnings (cf. Butler et al, 2012a). If trust behavior, in turn, varies positively with trust beliefs and individuals have self-interested money-maximizing preferences and, moreover, are interacting with a fixed population, one would expect earnings to be maximized when beliefs are correct: Miscalibrated trust beliefs should only reduce economic performance.…”
Section: The Economic Cost Of False Consensusmentioning
confidence: 99%
“…Recently, a study by Butler et al (2016) identified an inverse U-shape relationship between generalized trust and income, according to which each society has an income maximizing level of trust. Individuals with too little trust, thus located to the left of the income maximizing level of trust, may miss out on profitable opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in this paper, we are especially interested in the mass of "overly trusting" individuals that Butler et al (2016) documented. We posit and show that the wellbeing maximizing level of trust is consistently higher than the income maximizing level of trust.…”
Section: Introductionmentioning
confidence: 99%
“…Trustworthiness is the opposite side of the coin: If most people in a country are trustworthy, trusting people is a good rule of thumb for economic agents as this will facilitate transactions and exchange in the economy. The calculation changes if most people are not trustworthy, as someone who trusts people is then likely to fall prey to opportunistic behavior (Butler et al 2016); however, a mean national level of generalized trust that does not correspond to a mean level of trustworthiness is unlikely to be sustainable since trusting people eventually adjust their beliefs downward (Bjørnskov 2007). That said, if a country has a sufficiently high proportion of trustworthy people, generalized trust among its population might spontaneously evolve, provided that people are rational and not too risk averse (Hardin 1996, p. 29).…”
Section: Trust and Entrepreneurshipmentioning
confidence: 99%